Effect of physical exercise and age on knee joint position sense - Fernando Ribeiro (2010)
This study aimed to test the hypotheses that knee position sense declines with age and that regular exercise can attenuate that decline. This cross-sectional study encompassed 69 older and 60 young adults divided in four groups (exercised-old, N = 31; non-exercised-old, N = 38; exercised-young, N = 35; non-exercised-young, N = 25) according to chronological age and exercise practice in the past year. Knee position sense was measured by open kinetic chain technique and active positioning and is reported as the absolute and relative angular error. Knee angles were determined by computer analysis of videotape images using the Ariel Performance Analysis System. Compared to their non-exercised counterparts, exercised-young and -old showed lower absolute and relative angular errors. The absolute (1.62 + 0.71 degrees) and relative errors (0.02 +/- 1.65 degrees) for exercised-young were lower than all other groups (p < 0.001). The absolute and relative errors of exercised-old (4.27 +/- 2.49 degrees and 5.51 +/- 3.42 degrees) were similar to non-exercised-young (4.74 +/- 2.67 degrees and 4.18 +/- 3.40 degrees). The non-exercised-old exhibited higher absolute (9.35 +/- 4.34 degrees) and relative errors (9.73 +/- 5.15 degrees) than all other groups (p < 0.001). The present data indicates that age has deleterious effects on knee position sense although regular exercise can attenuate that age-related decline.